Model bahan ajar membaca pemahaman berbasis teks dengan pendekatan content language integrited learning - Nurbaya, St; Rahayu, Dwi Hanti (Humanika: Kajian Ilmiah Mata Kuliah Umum, 2018)
This study aimed to develop reading material teaching based on text with a content language integrated learning approach for students of PBSI FBS UNY. Development design followed the design model developed by Willis, known as the R2D2 model (1995), with steps (1) defining 2) planning and development, 3) dissemination. Products whose developed are text-based reading teaching materials with the CLIL approach. The products have been assessed by peers, reading learning experts, and lecturers of reading comprehension courses. There are five types of texts developed into teaching materials, namely; 1) description text, exposition text, argumentation text, editorial text, and research proposal text. Each text is used as a learning unit. Each learning unit was divided into; 1) learning objectives, 20 teaching materials, 3) texts, and 4) evaluation of learning. The assessment instrument used the teaching material assessment rubric with 4 components, scaled 1-4. The four assessment components; 1) content eligibility with a mean value of 23.00 or with a very good category, 2) language with a mean value of 14.00 or good category, 3) presentation with a mean of 19.30 or in a very good category while the component, 4) the design gets a mean value of 14.60 or good category. Overall, research development on instructional materials is at an average rate of 17.72 or a good category.Penelitian ini bertujuan mengembangkan bahan ajar membaca pemahaman berbasis teks dengan pendekatan content language integrited learning untuk mahasiswa PBSI FBS UNY. Desain pengembangan mengikuti model desain yang dikembangkan oleh Willis yang lebih dikenal dengan model R2D2 (1995,) dengan langkah (1) pendefinisian 2) perencanaan dan pengembangan, 3) penyebarluasan. Produk temuan hasil pengembangan adalah bahan ajar membaca berbasis teks dengan pendekatan CLIL. Produk telah dinilai oleh teman sejawat, pakar pembelajaran membaca, dan dosen-dosen mata kuliah membaca pemahaman. Jenis teks yang dikembangkan menjadi bahan ajar ada lima, yaitu; 1) teks deskripsi, teks ekposisi, teks argumentasi, teks editorial, dan teks proposal penelitian. Masing-masing teks dijadikan unit pembelajaran. Tiap unit pembelajaran terbagi atas ; 1) tujuan pembelajaran, 20 materi ajar, 3) teks yang dibaca, dan 4) evaluasi pembelajaran. Instrumen penilaian menggunakan rubrik penilaian bahan ajar dengan 4 komponen yakni berskala 1-4. Keempat komponen penilaian meliputi; 1) kelayakan isi dengan rerata nilai 23.00 atau dengan kategori sangat baik , 2) kebahasaan dengan rerata nilai 14.00 dan terkategori baik, 3 ) penyajian dengan rerata 19.30 atau berada pada kategori sangat baik, sedangkan komponen , 4) desain mendapatkan rerata nilai 14.60 dengan kategori baik. Secara keseluruhan, penelitian terhadap bahan ajar hasil pengembangan berada pada angka rerata 17,72 atau berada pada kategori baik.